Further cases of poisoning of wild geese by an organophosphorus winter wheat seed treatment - Hamilton, G A; Stanley, P I (Wildfowl, 1975)
A series of incidents involving Greylag Goose Anser anser casualties in Angus and Perthshire and a single incident involving Pink-footed Goose Anser brachyrhynchus casualties on Humberside are described. A full field and laboratory investigation revealed that the geese had died of organophosphorus poisoning after consuming winter wheat treated with carbophenothion. The factors that led to the incidents are discussed.